Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

If $n=p_1^{k_1}p_2^{k_2}\cdots p_r^{k_r}$then ,show the inequality :$$ \sigma(n) \phi(n) \geq n^2(1-\frac{1}{p_1^2})(1-\frac{1}{p_2^2})\cdots(1-\frac{1}{p_r^2})$$

I know the function $\sigma(n) \phi(n)$ is multiplicative hence I only have to show the inequality for $n=p^{k}$
So $$\sigma(n) \phi(n)$$ $$\implies \frac{n(p^{k+1}-1)}{p}$$ But after then how to get the desired inequality?

share|improve this question
1  
$n\frac{p^{k + 1} - 1}{p} = n\left( p^k - \frac{1}{p} \right) = n\left( n - \frac{1}{p} \right) = n^2\left( 1 - \frac{1}{np} \right) \geq n^2\left( 1 - \frac{1}{p^2} \right)$ –  TenaliRaman Jun 16 '12 at 14:33

1 Answer 1

up vote 5 down vote accepted

Putting $n = p^k$, $\sigma(n)\phi(n) = \frac{p^{k + 1} - 1}{p - 1} p^{k -1}(p - 1) = p^{2k} - p^{k - 1}$ and $n^2 (1 - \frac{1}{p^2}) = p^{2k} - p^{2k - 2}$.

So we get the inequality and furthermore we see that equality happens iff k = 1. Thus for a general $n$ the equality happens iff $n$ is squarefree.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.